A Review of the Research in Islamic Education in Indonesia Through the Vosviewer Application - Dananier, Nabella; Hadi, Syamsul; R. M. D. A. Dwisatria; Ibrahim, Muhammad Yusuf; Amali, S. R. Mutia; Maulida, Syah Datul (PT Inovasi Pratama Internasional, 2024)
Islamic education is an educational system that focuses on teaching Islamic values, and religious teachings, as well as spiritual and moral development in the context of learning. Islamic education has a key role in forming Muslim individuals who understand, practice, and spread the values of the Islamic religion in everyday life and contribute to the development of a civilized and harmonious society. This research aims to present an overview of research developments in the field of Islamic education in Indonesia using the VOSviewer application. The data analyzed were 500 research publications on Islamic education indexed by Dimensions. Bibliometric analysis methods are used to collect data from related articles published within a certain period. The study indicates that research related to Islamic education in Indonesia has experienced an increase during the period from 1965 to 2023, with an annual growth rate of 3.86%. This signifies significant interest in this topic. Ismail Suardi Wekke has been identified as the most influential researcher with 7 published articles. Among the core journals, the Journal of Islamic Education stands out by publishing 20 documents related to the research theme. Keyword network analysis has yielded several research streams, including education on anti-corruption leadership, improvement of digital literacy in elementary schools, entrepreneurship and economics education in Islamic boarding schools, and enhancement of Sharia financial literacy in schools. The study also provides a number of potential research agendas for the future concerning Islamic education in Indonesia.